2005
DOI: 10.1084/jem.20041672
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic role of micronemal proteins in Toxoplasma gondii virulence

Abstract: Apicomplexan parasites invade cells by a unique mechanism involving discharge of secretory vesicles called micronemes. Microneme proteins (MICs) include transmembrane and soluble proteins expressing different adhesive domains. Although the transmembrane protein TRAP and its homologues are thought to bridge cell surface receptors and the parasite submembranous motor, little is known about the function of other MICs. We have addressed the role of MIC1 and MIC3, two soluble adhesins of Toxoplasma gondii, in invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 29 publications
4
114
0
4
Order By: Relevance
“…function for attachment and initiation of invading processes (Soldati et al 2001;Cérède et al 2005;Ravindran and Boothroyd, 2008). Here we have demonstrated that NcMIC2-like1 is mainly located in the apical region of the tachyzoite, possibly in the micronemes, such as demonstrated for NcMIC2 (Lovett et al 2000), TgMIC2 , TgMIC 3 (El-Hajj et al 2008) and NcAMA 1 (Zhang et al 2006).…”
Section: Discussionsupporting
confidence: 56%
“…function for attachment and initiation of invading processes (Soldati et al 2001;Cérède et al 2005;Ravindran and Boothroyd, 2008). Here we have demonstrated that NcMIC2-like1 is mainly located in the apical region of the tachyzoite, possibly in the micronemes, such as demonstrated for NcMIC2 (Lovett et al 2000), TgMIC2 , TgMIC 3 (El-Hajj et al 2008) and NcAMA 1 (Zhang et al 2006).…”
Section: Discussionsupporting
confidence: 56%
“…T. gondii excretory/secretory antigens (ESAs) are an excellent serological marker for the diagnosis of CT in AIDS patients (Pereira-Chioccola et al, 2009). ESAs are produced by T. gondii tachyzoites, the form responsible for disease dissemination, which plays an important role in stimulating humoral and cellular immunities in order to control Toxoplasma infection (Carruthers & Sibley, 1997;Cérède et al, 2005). Anti-ESA IgG antibodies are also present in C S F s a m p l e o f A I D S p a t i e n t s w i t h C T w h i c h c a n b e d e t e r m i n e d b y E S A -E L I S A a n d immunoblot techniques and these samples are clearly distinguishable from AIDS patients who are Toxoplasma seropositive but with other brain diseases (Pereira-Chioccola et al, 2009).…”
Section: Serological Diagnosismentioning
confidence: 99%
“…2A; Friedrich et al 2010); and recognition of host carbohydrates mediated by an N-terminal domain within the microneme-secreted proteins MIC3 and MIC8 (CBL domain shown in TGME49_286740, Fig. 2A) during host cell invasion by Toxoplasma tachyzoites (Céréde et al 2005). These carbohydrate-binding domains appear to be specific to 1 or more apicomplexan genera and are not found in proto-apicomplexans.…”
Section: Introductionmentioning
confidence: 99%